CHRONIC KIDNEY DISEASE IN PATIENTS WITH RESISTANCE HYPERTENSION AND ACHIEVEMENT OF TARGET BLOOD PRESSURE. (April 2021) - Rekovets, Oksana; Torbas, Olena; Kushnir, Svitlana; Primak, Galina; Krushynska, Nina; Granich, Vladimir; Sirenko, Yuriy
Abstract : Objective: Glomerular filtration rate (eGFR) drop in patients with resistant hypertension and how different factors can affect on achievement of target blood pressure in patients with resistant hypertension and chronic kidney disease (CKD). To evaluate factors related with achievement of target blood pressure in patients with resistant hypertension and CKD. Design and method: We included 1134 patients who taken 3 or more antihypertensive drugs: first group (n = 877) patients with RH and eGFR (CKD-EPI) > = 60 ml/min/1.73 m2 a mean age of 53.5 ± 7.1 years, and second group (n = 257) patients with RH and eGFR (CKD-EPI) < 60 ml/min/1.73 m2 a mean age 66.1 ± 8.5 years, SBP 172.8 ± 8.2 and DBP 101.2 ± 6.3mmHg. Patients with secondary arterial hypertension was excluded. Results: 513 patients (58.5%) with eGFR > = 60 ml/min/1.73 m2 and achievement target office BP and 233 patients (41.5%) not achievement target office BP. 140 patients (54.5%) with eGFR < 60 ml/min/1.73 m2 and achievement target office BP and 117 patients (45.5%) not achievement target office BP. Patients with CKD-EPI > = 60 ml/min/1.73 m2 and achievement BP had higher blood renin (324.5 ± 23.3) ng/l vs not achievement BP (23.2 ± 3.5) ng/l (p < 0.05). Patients with CKD-EPI > = 60 ml/min/1.73 m2 and achievement BP had low blood cortisol level (47.8 ± 3.4) mkg/dl vs patients not achievement BP (163.7 ± 7.8) mkg/dl (p < 0.05). Aldosterone blood level was similar in both group 26.7 ng/dl vs 28.1 ng/dl respectively. Patients with CKD-EPI < 60 ml/min/1.73 m2 and achievement BP had low blood renin (34.1 ± 3.6) ng/l as patients not achievement BP (26.8 ± 2.5) ng/l (p > 0.05). Patients with CKD-EPI < 60 ml/min/1.73 m2 and achievement BP had low blood cortisol (6.0 ± 0.6) mkg/dl vs patients not achievement BP (127.7 ± 8.6) mkg/dl (p < 0.05). Conclusions: In patients with RH and CKD-EPI < 60 ml/min/1.73 m2 factors related with not achievement target BP was higher blood cortisol. In patients with RH and CKD-EPI > = 60 ml/min/1.73 m2 factors related with not achievement target BP was low blood renin level and higher blood cortisol.